Anthropometric characteristic, body composition and somatotype of canadian female soccer players - Adhikari, A.; Nugent, J. (American Journal of Sports Science, 2014)
Canadian female junior soccer players were evaluated for their anthropometrical characteristics including somatotype and body composition with a aim to evaluate with their international counterparts. 18 female soccer players with an average age of 16(±0.5) of a local club were assessed during their peak season time. Somatotype was assessed using Heath-Carter method and body composition ( Fat%) was assessed by surface anthropometry . Endomorphic mesomorph (3.0 ±0.8 - 3.9±0.8 -2.58±1.0 ) body type was observed in average with an average 22.1(±3.1) % body fat. Average waist-hip ratio was 0.7 (±0.03) . Though BMI does not reflect the obesity precisely in athletic population, average BMI of the female soccer group was in normal range with an average value of 21.5 (±1.8) kg.m-2 .Thus the Canadian junior female soccer players possessed an average muscularity with slightly higher fat % compare to national level female athletes . The group needed more muscularity with less fattiness.